2015
DOI: 10.1371/journal.pone.0129669
|View full text |Cite
|
Sign up to set email alerts
|

Adjustments of the Pesticide Risk Index Used in Environmental Policy in Flanders

Abstract: Indicators are used to quantify the pressure of pesticides on the environment. Pesticide risk indicators typically require weighting environmental exposure by a no effect concentration. An indicator based on spread equivalents (ΣSeq) is used in environmental policy in Flanders (Belgium). The pesticide risk for aquatic life is estimated by weighting active ingredient usage by the ratio of their maximum allowable concentration and their soil halflife. Accurate estimates of total pesticide usage in the region are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
6
2
Order By: Relevance
“…Also, more than three quarters follow the light wind direction of spraying. These findings are not consistent with a result of [23] in their study about "adjustments of the pesticide risk index used in environmental policy in Flanders" indicated that pesticides were commonly applied during day time, but very few paid attention to the wind direction during pesticide application.…”
Section: Discussioncontrasting
confidence: 65%
“…Also, more than three quarters follow the light wind direction of spraying. These findings are not consistent with a result of [23] in their study about "adjustments of the pesticide risk index used in environmental policy in Flanders" indicated that pesticides were commonly applied during day time, but very few paid attention to the wind direction during pesticide application.…”
Section: Discussioncontrasting
confidence: 65%
“…ΣSeq is an ecotoxicity indicator that calculates the pressure from using pesticides for agricultural and non-agricultural purposes (vector control) in aquatic organisms (De Smet & Steurbaut, 2002;Fevery et al, 2015). This indicator was included in this study, as POCER considers that the drift of pesticides mainly causes the exposure of aquatic organisms.…”
Section: Equation 11mentioning
confidence: 99%
“…The MAC values are calculated by dividing the lowest toxicity value (representative for aquatic organisms, i.e., the acute or chronic toxicity up to three trophic levels: EC50algae, NOECalgae, LC50crustaceans, NOECcrustaceans, LC50fish, and NOECfish) by safety factor "10", as done by Fevery et al (2015).…”
Section: Equation 11mentioning
confidence: 99%
See 2 more Smart Citations